Characteristics of rice husk tar pyrolysis by external flue gas. (14th September 2015) - Zhai, Ming; Wang, Xinyu; Zhang, Yu; Dong, Peng; Qi, Guoli
Abstract: Biomass tar is a major problem in both pyrolysis and gasification of biomass. Considering the process and conditions of tar formation, an external flue gas pyrolysis system for rice husk tar pyrolysis was designed. The characteristics of rice husk tar pyrolysis by external flue gas were investigated. The GC–MS analysis was applied to analyze the composition of rice husk tar and its distillate. TGA was carried out to investigate the properties of rice husk tar and its distillate. Results show that when the temperature is below 500 °C, the liquid product of rice husk pyrolysis is rice husk oil; when the temperature reaches about 700 °C, PAHs increase significantly and the liquid product is tar; when the temperature reaches 800 °C, a large amount of charcoal liquid is produced. There are many similarities between rice husk tar and its distillate. After distillation, the content of the primary compounds like naphthalene, anthracene, phenol and its derivative increases, while the content of fluorene and phenanthrene decreases. Temperature plays an active role in the pyrolysis of rice husk oil and tar, and the proportion of compounds in the pyrolysis product. The weight loss of rice husk tar distillate can be divided into three regions, and it reaches a maximum at about 160 °C. The experimental data provide a reference to the optimization of the operating conditions for rice husk pyrolysis and tar cracking. Graphical abstract: Highlights: External high-temperature anaerobic flue gas was used for rice husk tar pyrolysis. An external flue gas pyrolysis system for rice husk tar pyrolysis was designed. Rice husk tar pyrolysis characteristics and properties of the tar were investigated. The liquid product of rice husk pyrolysis is oil below 500 °C, and is tar at 700 °C. The weight loss of rice husk tar distillate reaches a maximum at about 160 °C.